2019
DOI: 10.1007/s40429-019-00254-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Automatically Activated Approach–Avoidance Biases Across Appetitive Substances

Abstract: Purpose of Review Automatic approach-avoidance tendencies drive excessive intake of drugs and unhealthy food. Dual-process models of behaviour propose that strong approach biases predict excessive intake when reflective processes are weak. Consistent with theory, early findings indicated that approach biases predicted excessive use of drugs, including alcohol and tobacco. Given that reviews on approach bias for appetitive substances are lacking, the current review aimed to synthesise the recent findings on aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 90 publications
(128 reference statements)
0
10
0
Order By: Relevance
“…Building upon dual-process theories [11, 12], addictions have been explained by an excess of (implicit) impulsive approach tendencies that override the (explicit) will to disengage from the behavior and the explicit insight into the harmful potential of a substance or behavior [13]. In keeping with these findings, experimental studies using the approach-avoidance task (AAT) show that addicted individuals are faster to pull a picture of their preferred drug toward themselves than to push it away via a joystick in a computerized setup compared to non-addicted individuals [14]. This effect is especially well-established in alcohol addiction, but similar findings have been obtained in smoking, too.…”
Section: Introductionmentioning
confidence: 99%
“…Building upon dual-process theories [11, 12], addictions have been explained by an excess of (implicit) impulsive approach tendencies that override the (explicit) will to disengage from the behavior and the explicit insight into the harmful potential of a substance or behavior [13]. In keeping with these findings, experimental studies using the approach-avoidance task (AAT) show that addicted individuals are faster to pull a picture of their preferred drug toward themselves than to push it away via a joystick in a computerized setup compared to non-addicted individuals [14]. This effect is especially well-established in alcohol addiction, but similar findings have been obtained in smoking, too.…”
Section: Introductionmentioning
confidence: 99%
“…Given these promising findings, it is unfortunate that many of the above effects have failed to be consistently replicated (for overviews, see Kakoschke et al, 2019 and Loijen et al, 2020 ). For example, using the same methods as Ernst et al ( 2014 ), Wiers et al ( 2017 ) did not find stronger alcohol approach tendencies in alcohol-dependent compared to healthy participants.…”
mentioning
confidence: 99%
“…The alcohol approach bias was observed in patients during inpatient withdrawal treatments [24,60]. However, when considering other measurements such as stimulus-response compatibility (SRC) task, several previous studies reported no approach bias or even an avoidance bias to alcohol stimuli in AD patients (compared to controls) after detoxification [52,61,62]. These inconsistent findings may be explained by differences in assessment tasks, how the approach bias was calculated, or may be due to differences in sample characteristics, including patients' drinking status and treatment seeking motivation [63].…”
Section: Discussionmentioning
confidence: 99%